Comparative Study of Sun Drying and Solar Tent Drying of Hyperopisus bebe occidentalis - Ojutiku, R.O.; Kolo, R.J.; Mohammed, M.L. (Pakistan Journal of Nutrition, 2009)
An experiment was conducted to investigate the effect of two drying processing methods on the nutritional qualities of Hyperopisus bebe. The two methods used were solar tent dryer and traditional sun drying methods. The experimental fish were dried for 120 h (5 days). The results of proximate analysis showed significant difference (p